EVALUASI DRUG RELATED PROBLEMS PADA PASIEN GERIATRI DENGAN HIPERTENSI DISERTAI VERTIGO DI RS PANTI RINI YOGYAKARTA AGUSTUS 2013 - Kresensiana Yosriani; Maria Wisnu Donowati; Aris Widayati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2014)
Abstract : This study aimed to evaluate Drug Related Problems (DRPs) among hypertensive geriatricpatients with vertigo co morbid at Panti Rini Hospital Yogyakarta. This is a non-experimental researchdescriptive evaluative design using a retrospective medical record data. Collected data including patient'sidentity; initial, final, and complication diagnosis; cardiovascular system drugs and antivertigo,laboratory data. The inclusion criteria were ? 60 years with an initial diagnosis of hypertension withvertigo co morbid, used a diuretic drug, and had creatinine test result. Data were analyzed case by caseusing selected literatur. There were 20 cases found. Result of the study showed that 100% of patients usedantihypertensive as the cardiovascular system drugs and 80% patients used antivertigo as nervous systemdrugs. There were 18 cases of DRPs found related to the use of antihypertensive and antivertigo. 1 case ofdosage too low, 8 cases of adverse drug reaction, and 9 cases of dosege too high.Keywords : hypertension with vertigo co morbid, geriatrics, Drug Related Problems